Hamiltonian analysis of accurate integration of a three-level quantum model of the Dicke super-radiation - Samulyak , R. V. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
It is proved, that the quantum З-level supperradiance Dicke model is exactly solvable. The Lax representation of the evolutionary equations system is derived basing on the theory of current Lie algebras. The quantum inverse scattering problem method is used to obtain quantum analogues of the action-angle variables. The spectra of the energy operator and the other quantum integrals of motion is constructed as well as the exact one- and multiparticles excitation eigenstates of the model. It is shown, that model possesses the states of constrained’ quasiparticles (quantum solitons), which involve the supperradianse pulses.